UMBRELLA CLAUSE IN INVESTMENT DISPUTES: THE ISSUE OF PERSONAL SCOPE - Đundić, Petar (Zbornik radova Pravnog fakulteta u Novom Sadu, 2026)
The issue of interpretation given to umbrella clauses – provisions of bilateral or multilateral investment protection treaties by which states accept duty to observe any obligation entered into with respect to the investments of the investors of the other state party – represents one of the most controversial issues in practice of investment tribunals. Ever since the tribunal in SGS v. Philippines rendered its award accepting that a breach of an investment contract by a state can, under certain conditions, signify a breach of its international law obligation embodied in the umbrella clause, some investment tribunals and host states have been engaged in an effort to limit effects of the clause. The aim of this paper is to analyze the practice of investment tribunals with regard to the particular issue of the clause’s personal scope. According to the current state of arbitral practice, the most significant obstacle to the success of claimants whose claims are based on umbrella clauses concerns the understanding that investor-state contracts produce effects only for its contracting parties (the so-called privity requirement). In the absence of an umbrella clause with peculiar wording, an investor may base his claim on a contract concluded by his subsidiary or on a contract concluded with an entity outside of the host state’s formal structure only if this is provided for by the contract itself or by the national law applicable to the contract. Although this view is not universally accepted in arbitral practice it consistently distinguishes between the obligations of a state arising from the application of national law, on the one hand, and obligations that have their origin in international law, on the other. It is also consistent with the role that arbitral tribunals give to the national law of host states when applying other substantive standards of investment protection.
Keywords: : umbrella clause, protection of foreign investments, investment disputes, bilateral investment treaties.